Implementasi Peraturan Bupati Banyuwangi Nomor 59 Tahun 2017 Tentang Penyelenggaraan Mal Pelayanan Publik - Dimas Imaniar (FISIP UWP, 2023)
The Banyuwangi district government is currently always faced with limitations and challenges, starting with matters of budget, human resources, authority, to time. These limitations and challenges then gave birth to two solutions, namely innovation and collaboration.